Low socio-economic status associated with increased risk of dengue haemorrhagic fever in Taiwanese patients with dengue fever: a population-based cohort study. (5th November 2019) - Lai, Yun-Ju; Lai, Hsin-Hao; Chen, Yu-Yen; Ko, Ming-Chung; Chen, Chu-Chieh; Chuang, Pei-Hung; Yen, Yung-Feng; Morisky, Donald E
Abstract: Background: Evidence indicates that socio-economic status (SES) may affect health outcomes in patients with chronic diseases. However, little is known about the impact of SES on the prognosis of acute dengue. This nationwide cohort study determined the risk of dengue haemorrhagic fever (DHF) in Taiwanese dengue fever patients from 2000 to 2014. Methods: From 1 January 2000, we identified adult dengue cases reported in the Taiwan Centers for Disease Control Notifiable Diseases Surveillance System Database. Dengue cases were defined as positive virus isolation, nucleic acid amplification tests or serological tests. Associations between SES and incident DHF were estimated using a Cox proportional hazards model. Results: Of 27 750 dengue patients, 985 (3.5%) had incident DHF during the follow-up period, including 442 (4.8%) and 543 (2.9%) with low and high SES, respectively. After adjusting for age, sex, history of dengue fever and comorbidities, low SES was significantly associated with an increased risk of incident DHF (adjusted hazard ratio [AHR] 1.61 [95% confidence interval CI 1.42 to 1.83]). Rural-dwelling dengue patients had a higher likelihood of DHF complication than their urban counterparts (AHR 2.18 [95% CI 1.90 to 2.51]). Conclusions: This study suggests low SES is an independent risk factor for DHF. Future dengue control programs should particularly target dengue patients with low SES for improved outcomes.